The Interaction of Students with Cognitive Problems in the Learning Process of English as a Foreign Language (FL) in a Colombian public school (2016)
This research aimed at describing the impact, either negative or positive, students with cognitive impairments have on students who do not present such difficulties in a classroom where inclusion and the learning of English as a foreign language (EFL) are fostered. This investigation was conducted in Santa Teresa de Jesús Public High School, which is located in the east of Armenia city, Quindío, Colombia. Thus, one of the sixth level groups was the basis for the application of the different instruments (Interviews, Observations, and Archival Documents) and the data collection. Consequently, this study happens to be comprised of qualitative data. Will all this, inclusion was found to be a determinant factor toward the learning of EFL. First, and in 3 general terms, students with normal capacities seem not to be affected negatively in the learning process of EFL. On the contrary, and in more specific terms, students with cognitive difficulties do not display improvement in such foreign language, since what inclusion does is strengthening the cognitive-impaired students´ social skill, but they do not obtain a meaningful learning process in the linguistic skills.